2021
DOI: 10.1186/s12951-021-01154-2
|View full text |Cite
|
Sign up to set email alerts
|

Single cell sequencing analysis identifies genetics-modulated ORMDL3+ cholangiocytes having higher metabolic effects on primary biliary cholangitis

Abstract: Background Primary biliary cholangitis (PBC) is a classical autoimmune disease, which is highly influenced by genetic determinants. Many genome-wide association studies (GWAS) have reported that numerous genetic loci were significantly associated with PBC susceptibility. However, the effects of genetic determinants on liver cells and its immune microenvironment for PBC remain unclear. Results We constructed a powerful computational framework to int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 94 publications
1
20
0
Order By: Relevance
“…The power of this study is limited by the lack of matched genetic data and scRNA-seq data in each sample for uncovering the genetic effects on immune cells for severe COVID-19. To reduce the influence of this limitation, we adopted a widely used approach by integrating a large-scale GWAS summary statistics with an enormous amount of single-cell sequencing data, as referenced in previous studies [ 49 , 89 , 90 ]. As referenced to previous studies [ 91 – 94 ], we excluded the major histocompatibility complex (MHC) region from all genomic analyses to avoid the confounding of methods by the unusual genetic architecture and extensively high levels of LD at this locus, which could lead to the inflation of identified COVID-19-associated genes and pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The power of this study is limited by the lack of matched genetic data and scRNA-seq data in each sample for uncovering the genetic effects on immune cells for severe COVID-19. To reduce the influence of this limitation, we adopted a widely used approach by integrating a large-scale GWAS summary statistics with an enormous amount of single-cell sequencing data, as referenced in previous studies [ 49 , 89 , 90 ]. As referenced to previous studies [ 91 – 94 ], we excluded the major histocompatibility complex (MHC) region from all genomic analyses to avoid the confounding of methods by the unusual genetic architecture and extensively high levels of LD at this locus, which could lead to the inflation of identified COVID-19-associated genes and pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Using single-cell RNA sequencing (scRNA-seq) techniques, Poch and colleagues generated the first atlas of intrahepatic T cells in PSC and identified a previously uncharacterized population of liver-resident CD4 + T cells that likely contribute to the pathogenesis of PSC [ 84 ]. Xiang and colleagues [ 85 ] developed a computational framework to integrate GWAS summary statistics with scRNA-seq data and revealed genetically modulated liver cell subpopulations for PBC. They found that cholangiocytes show significant enrichment with PBC-related genetic association signals, with the ORMDL3 gene showing the highest expression level in cholangiocytes compared with other liver cells.…”
Section: Genetically Regulated Expression and Single Cell Analysesmentioning
confidence: 99%
“…As immune-mediated diseases, the immune cells recruited by cholangiocyte secretion significantly altered the composition of intrahepatic immune cells and are involved in disease pathogenesis and regulation of biliary repair ( 144 ). ScRNA-seq of liver of PBC patients indicated that ORMDL3 + cholangiocytes displayed higher interaction with immune cells such as macrophages and monocytes, which might play a role in the pathogenesis of PBC ( 145 ).…”
Section: Role Of Immune Cells In Biliary Repair In Cholangiopathiesmentioning
confidence: 99%